2001
DOI: 10.1002/bies.1062
|View full text |Cite
|
Sign up to set email alerts
|

The Tec family of cytoplasmic tyrosine kinases: mammalian Btk, Bmx, Itk, Tec, Txk and homologs in other species

Abstract: Cytoplasmic protein-tyrosine kinases (PTKs) are enzymes involved in transducing a vast number of signals in metazoans. The importance of the Tec family of kinases was immediately recognized when, in 1993, mutations in the gene encoding Bruton's tyrosine kinase (Btk) were reported to cause the human disease X-linked agammaglobulinemia (XLA). Since then, additional kinases belonging to this family have been isolated, and the availability of full genome sequences allows identification of all members in selected s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
251
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(256 citation statements)
references
References 86 publications
1
251
0
4
Order By: Relevance
“…Section 1734 solely to indicate this fact. 1 GFP fragment for YFP1-Itk or YFP2-Itk in the FUGW vector, respectively. The pGFP-Itk was generated by inserting GFP fragment to the N terminus of HA-Itk (24).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Section 1734 solely to indicate this fact. 1 GFP fragment for YFP1-Itk or YFP2-Itk in the FUGW vector, respectively. The pGFP-Itk was generated by inserting GFP fragment to the N terminus of HA-Itk (24).…”
Section: Methodsmentioning
confidence: 99%
“…The Tec family of non-receptor tyrosine kinases is the second largest family of non-receptor tyrosine kinases (1). This family, which includes Itk, 2 is involved in transducing signals from a number of receptors, including the T cell receptor, B cell receptor, Fc⑀R, c-Kit, CD28, CD2, CD32, and the erythropoietin receptor (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that a more complete block in NK T cell development does not occur may be due to compensation by other family members. Itk is a member of a larger gene family, that includes Rlk and Tec, both of which are expressed in T and NK cells (47). It has been shown that mice doubly deficient in itk and rlk show increased deficiencies in conventional T cell development compared with the single mutations (48).…”
Section: The Role Of Itk In Nk T Cell Ontogenymentioning
confidence: 99%